The tragedy of scientific culture: Husserl on inauthentic habits, technisation and mechanisation - Arnold, Thomas (Human studies, 2022)
Habit and habitualisation play an important role in Husserl's phenomenology, yet one aspect of habituality has been somewhat overlooked, namely the dimension of authenticity/inauthenticity. While authenticity in Heidegger has received a lot of attention, inauthenticity in Husserl is less well researched, although, as I will show, it is of equal importance to his overall theorising. The central aim of this paper is to explore the authenticity/inauthenticity-distinction in the various domains of habitualisation and to establish its fundamental importance for Husserl. In the first, introductory part of this paper I offer a few remarks on how to understand and categorise Husserl's transcendental take on habits; I also introduce the important distinction between authentic and inauthentic habits and authenticity and inauthenticity in general. In the second part I present the problem of mechanisation as a form of inauthentic habitualisation as it appears in Husserl's phenomenologies of ethics and, more importantly, science. The third part concludes the paper with a reflection on how phenomenology is programmatically aimed against any form of inauthenticity, and on how it might or might not achieve this goal.